Effects of NRAS Mutations on Leukemogenesis and Targeting of Children With Acute Lymphoblastic Leukemia - Qian, Jiabi; Li, Zifeng; Pei, Kunlin; Li, Ziping; Li, Chunjie; Yan, Muxia; Qian, Maoxiang; Song, Yuanbin; Zhang, Hui; He, Yingyi (Frontiers in Cell and Developmental Biology, 2022)
Through the advancements in recent decades, childhood acute lymphoblastic leukemia (ALL) is gradually becoming a highly curable disease. However, the truth is there remaining relapse in ∼15% of ALL cases with dismal outcomes. RAS mutations, in particular NRAS mutations, were predominant mutations affecting relapse susceptibility. KRAS mutations targeting has been successfully exploited, while NRAS mutation targeting remains to be explored due to its complicated and compensatory mechanisms. Using targeted sequencing, we profiled RAS mutations in 333 primary and 18 relapsed ALL patients and examined their impact on ALL leukemogenesis, therapeutic potential, and treatment outcome. Cumulative analysis showed that RAS mutations were associated with a higher relapse incidence in children with ALL. In vitro cellular assays revealed that about one-third of the NRAS mutations significantly transformed Ba/F3 cells as measured by IL3-independent growth. Meanwhile, we applied a high-throughput drug screening method to characterize variable mutation-related candidate targeted agents and uncovered that leukemogenic-NRAS mutations might respond to MEK, autophagy, Akt, EGFR signaling, Polo−like Kinase, Src signaling, and TGF−β receptor inhibition depending on the mutation profile.